Pengaruh Penggunaan Media Buku Cerita Terhadap Kemampuan Membaca Siswa Kelas IV Madrasah Ibtidaiyah di Banjarmasin - dan Yati, Noor Laila Alfu (IAIN Antasari Banjarmasin, 2014)
Reading is one of the important aspects in learning. Another important aspect in learning is learning media. The use of learning media in the teaching and learning process may generate desires, interests, motivation, and stimulate learning activities for students. However, most teachers today teach in a conventional learning with no use of learning media.Employing experiment method, this study is conducted to determine whether there is a difference in the academic achievement between students taught using the story books media compared to students taught without using the story books media. The subject of the study is the 4th grade students of MI Al-Istiqomah Banjarmasin. The data is drawn from the score of pre-test which is done before the process of learning and the score of final test.The result of the study shows that there is a significant difference between the academic achievements of students who are taught using the story books media compared to the students taught with no use of any media in their reading comprehension subject. This is indicated by the mean score of the final testâthe study result in the experimental class is better than that of the controlled class. Thus, it can be concluded that learning with using the media of story books can improve the studentsâ study result. In addition, the learning media can be an alternative for the teachers in the process of teaching and learning.